The shale oil boom and comprehensive wealth of the Bakken region of North Dakota. Issue 5 (19th October 2020) - Kim, Jinhyoung; Johnson, Thomas G.
ABSTRACT: This study applies the comprehensive wealth framework (CWF) to assess the impacts of the Bakken shale oil boom on the wellbeing of people in North Dakota. In particular, we consider how investment in shale oil and gas production has affected financial and natural capital and how in-migrants and commuters have affected the region's social, built, and human capital. We conclude that much of the economic benefits have accrued to new residents and nonresidents and that temporary employment in the gas and oil sector has coincided with increased housing cost, violent crime, decreased volunteerism, and declining regional social capital, potentially reducing the comprehensive wealth of long-time residents.